Viva Zapata! Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Emiliano Zapata (Marlon Brando) walks with his hands bound behind him, attached by a rope around his neck to one of two horses ahead of him as other horsemen trail behind. RESTRICTED USE